2011
DOI: 10.1002/lary.22354
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal electromyography for prognosis of vocal fold palsy: A Meta‐Analysis

Abstract: LEMG is a good predictor of poor recovery in patients with VFP and is clinically useful in identifying candidates for early definitive intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 18 publications
2
73
0
9
Order By: Relevance
“…On the other hand, if the vocal process of the paralysed arytenoid is placed higher than the normal vocal fold, the inferior and medial displacement of the vocal process achieved by arytenoid adduction should be beneficial. 8,14 Our findings are comparable with those of Hong and Jung; in their study, the variable vertical level of the affected side was explained based on the biomechanics of arytenoid cartilage movement over the convex facet of cricoid cartilage. 8 When the vertical height was equal, a medialisation laryngoplasty or thyroplasty was planned according to the glottic gap.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, if the vocal process of the paralysed arytenoid is placed higher than the normal vocal fold, the inferior and medial displacement of the vocal process achieved by arytenoid adduction should be beneficial. 8,14 Our findings are comparable with those of Hong and Jung; in their study, the variable vertical level of the affected side was explained based on the biomechanics of arytenoid cartilage movement over the convex facet of cricoid cartilage. 8 When the vertical height was equal, a medialisation laryngoplasty or thyroplasty was planned according to the glottic gap.…”
Section: Discussionsupporting
confidence: 92%
“…Rickert et al highlighted the potential importance of variables such as time of presentation, definition of recovery and duration of follow up, and a simplified concept of paralytic dysphonia. 14 Laryngeal electromyography can provide prognostic information about unilateral vocal fold paralysis, especially if it is conducted at least two months after symptom onset. 15 It can aid identification of normal innervation, the absence of innervation, reinnervation and even synkinesis, based on characteristic electrical signals.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, a working group of neurolaryngologists was created to reach a consensus regarding the guidelines for LEMG performance: indications, technique, interpretation of records and clinical application 5 . In 2012, a valid scientific article stated that the laryngeal electromyography is a good assessment in predicting the prognosis of recovery in patients diagnosed with vocal fold paresis and that it can help identify patients suitable for surgery 6 . It was also observed that the results of LEMG recordings repeatedly obtained on the same patient with neurologic diseases that affect the larynx are hardly reproducible 7 .…”
Section: Abstract: Electromyography Neurolaryngology Larynx Recurrmentioning
confidence: 99%
“…Laryngeal electromyography (LEMG) has been used to determine whether vocal fold immobility is of the neurogenic or mechanical type and to predict its prognosis (Heman-Ackah et al, 2006a,b;Munin et al, 2003;Rickert et al, 2012). However, LEMG has two main limitations: (1) the technical skill required for the examination, and (2) the utility of LEMG results to determine the prognosis of vocal fold immobility.…”
Section: Introductionmentioning
confidence: 98%